Basic income sustainability and productivity growth in cognitive capitalism: A first theoretical framework - Andrea Fumagalli; Stefano Lucarelli (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2006)
This paper aims at proposing a first theoretical framework for studying the basic income sustainability. We consider the basic income not only as a tool of a policy to improve living standards and social well-being but, mostly, as the essential requisite to introduce a new stable compromise between capital and labour. Following the French Regulation School approach, we assert that the social compromise between capital and labour is founded on the redistribution of the productivity gains. Therefore we try to trace living standards and social well being problems back to their origins, i.e. the productivity growth. We think that describing the dynamics of productivity means understanding the main features of the contemporary capitalistic production. We first present a survey about BI in economic literature. We then focus on the socio-economic transformation of western countries and propose the term cognitive capitalism (CC) to describe the economic system after the Fordism paradigm crisis, highlighting the strong links between the exploitation of knowledge and the accumulation of surplus. Therefore we investigate the presence of a new type of Kaldor-Verdoorn law in cognitive capitalism (a virtuous circle among BI, increasing productivity - via knowledge and network externalities - output and employment). As a result, we first point out the ambiguous growth circle of the contemporary capitalism. Secondly we highlight that BI is compatible with the new way of accumulation, based on the exploitation of dynamic scale economies. BI increases productivity, through network (externalities) and learning processes and, at the same time, demand, via consumption level. This double result is not always guaranteed. It depends, on one side, on how much BI positively affects productivity, and the greater this probability, the lower the role played by intellectual property rights and the higher the diffusion of network economies (general intellect and social cooperation); on the other side, it depends on the way BI is financed. These results also depend on the assumption of closed economy, in which financial markets play no role at all.
Keywords: I31; J24; 330; basic income; productivity; cognitive capitalism; crisis; Regulation School; Fordism; Post-fordism; knowledge; learning externalities; Kaldor-Verdoorn law; general intellect; Öffentliche Sozialleistungen; Produktivität; Wissensgesellschaft; Kapitalismus; Produktionssystem; Theorie